Optical coherence tomography angiography in retinitis pigmentosa - Hassairi, A.; Falfoul, Y.; Matri, K.; Ben Lassoued, O.; Chebil, A.; El Matri, L. (Acta ophthalmologica (Oxford, England), 2017)
Purpose The aim of this study is to describe macular vascular abnormalities in patients affected by retinitis pigmentosa using Optical coherence tomography angiography (OCT‐A). Methods Patients with a clinical diagnosis of retinitis pigmentosa underwent 3 × 3 Swept Source OCT‐A scans using a Swept‐Source DRI OCT Triton (Topcon Corporation, Japan). Scans with artifacts were excluded. Retinal vascular supply was estimated at the level of the superficial (SCP) and deep (DCP) capillary plexus, choriocapillaris and choroid. Results Six patients (12 eyes) were included in this study. Five were females (83.33%) and the mean age was 28.66 years. Mean best corrected visual acuity was 0.5 ± 0.3 LogMAR. Two patients presented bilateral macular edema on Swept Source‐OCT and showed focal dislocations in the vascular network at the level of the DCP on the OCT‐A, corresponding to the serous intraretinal cysts displacing the vascular plexus and the neural tissue. Qualitative analysis of OCT‐A at the macular area revealed a reduction of vessel density in the SCP and DCP. The DCP and especially the temporal area are more affected. Three patients (50%) showed an enlarged foveal avascular zone at the DCP level. Conclusions Using OCT‐A, we have demonstrated reduction of vessel densities especially located in the DCP. This vascular depletion could be an early event in the disease, which eventually causes ischemia, tissue loss and affects the macular function. Morphological vascular evaluation in patients affected by retinitis pigmentosa allows better understanding the pathogenesis of this disease and can have direct therapeutic implications for the future practical management of retinal dystrophies.